2018
DOI: 10.1007/s11749-018-0611-5
|View full text |Cite
|
Sign up to set email alerts
|

Mode testing, critical bandwidth and excess mass

Abstract: The identification of peaks or maxima in probability densities, by mode testing or bump hunting, has become an important problem in applied fields. This task has been approached in the statistical literature from different perspectives, with the proposal of testing procedures which are based on kernel density estimators or on the quantification of excess mass. However, none of the existing proposals provides a satisfactory performance in practice. In this work, a new procedure which combines the previous appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…During exploratory analysis, we noted possible multi-modality in the density distributions of bird and bat fall distances. To verify this observation, we performed non-parametric tests using the ACR method [58], as implemented by the multimode package [59] in R. We included all bird and bat records with fall distance information and values of 100 m or less. Our null hypothesis in these tests was unimodality, with α = 0.05.…”
Section: Plos Onementioning
confidence: 99%
“…During exploratory analysis, we noted possible multi-modality in the density distributions of bird and bat fall distances. To verify this observation, we performed non-parametric tests using the ACR method [58], as implemented by the multimode package [59] in R. We included all bird and bat records with fall distance information and values of 100 m or less. Our null hypothesis in these tests was unimodality, with α = 0.05.…”
Section: Plos Onementioning
confidence: 99%
“…We excluded variables with loadings below 0.30 [20]. Factor scores were investigated to determine whether they met the normality assumption and had a unimodal distribution [21]. Based on these analyses, the results of the factor scores are presented as median with interquartile ranges.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, Silverman () proposed to use as test statistic for H0 the smallest bandwidth such that the normal kernel density estimator has n0 modes and introduced a bootstrap procedure to calibrate the test. Different proposals were suggested by other authors, and a recent literature review about this problem can be found in Ameijeiras‐Alonso et al (). The same authors also developed the R package multimode (Ameijeiras‐Alonso et al , ), in which most of the existing procedures were implemented for their practical use.…”
Section: Many Modesmentioning
confidence: 99%